Penerapan Nilai Tauhid dalam Meningkatkan Kualitas Kehidupan Mahasiswa di Lingkungan Kampus UINSU - Muhammad Zali; Alifyah Ika Putri; Atika Zahra Harahap; Azyka Sofia; Chalieq Moestafidz; Fayza Rasyifa; Juan Syakir Haziq; Maurinda Cornelia Susilo; Nazla Alifa Kamal; Nazwa Septi Aini Lubis; Nesa Ariska; Nur Handayani; Rahma Aliifah Winfi; Shaiecka Radya Ruslan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This research aims to examine the application of the value of monotheism in shaping the character of students within the North Sumatra State Islamic University (UINSU). Through an in-depth study of the implementation of monotheism values ​​in students' daily lives, this research seeks to reveal the extent to which these values ​​have been internalized and their impact on students' quality of life. It is hoped that the research results can contribute to the development of a character development program based on monotheistic values ​​at UINSU. In the context of rapid modernization, the value of monotheism is often considered less relevant. This research aims to test this assumption by examining the implementation of the value of monotheism at UINSU. By analyzing how these values ​​are implemented and their impact on students, it is hoped that this research can fill the research gap regarding the relevance of the value of monotheism in the context of contemporary higher education.